POLITIK HUKUM MAHKAMAH KONSTITUSI SEBAGAI LEMBAGA JUDICIAL REVIEW - Faizal, Liky (JURNAL SOSIAL DAN HUMANIS SAINS, 2017)
The Constitutional Court is a new State institution resulting from the third amendment of the 1945 Constitution. The Constitutional Court is an independent institution in the judicial sector. The authority of Judicial Review is given to the Constitutional Court. The Constitutional Court is authorized to review the Act against the Constitution. From this it can be seen that one of the legal politics behind the birth of the idea of the establishment of the Constitutional Court is as an effort to anticipate the products of the authorities that can harm the interests of society. Therefore, the Constitutional Court is expected to exercise control with various authorities against various policies and products of governmental law in the form of legislation issued by the government so as not to conflict with the principles contained in the 1945 Constitution.